Klövviltets nyttjande av foderraps på viltåker och betespåverkan på angränsande skog - Lidberg, Maria (2011)
Today we have more game species than ever before in our landscape, both regarding number of species and number of individuals. The increasing number of wild species is an increase in game recourse for the countryside. The increase of game species, however, has negative effects on forests and agriculture land. The negative effects for forestry are damages on economic important trees, due to losses in production and quality. However there are ways to decrease the damage on valuable and important trees. One example is to reduce the wild species population by hunting, another alternative is to increase the available forage for the game. Also, an increase in production of forage may lead to less damage by game and hence reduce the conflict between different stakeholders, for example forestry production and hunters. There are a number of ways to increase the forage production. A common way in southern Sweden is to construct game fields with for the game attractive crops. The goal with this study was to determine if rapeseed (Brassica napus) is attractive as forage recourse for game species, which game species that utilize the resource and to estimate how much biomass a field of rapeseed can produce. The goal was also to investigate the impact of grazing on broadleaved trees and shrubs which grows in the forest close to the game field in distances from 0 to 500 meter from the game field. The study was made 2010, on ten game fields which had been sowed with rapeseeds in week 22 and 27. On the game fields I proportionally placed, based on the area of the field altogether 37 exclosures (1,6*1,6 m), each with a control plot. The position of each exclosure was decided with the help of a random table and a GPS. When the growth season ended in September the height and biomass was estimated for both rapeseed and weed in each exclosure and on the control plots. From every game field four transects was pointed out one from every cardinal destination (north, east, west and south). The transects was 500 meters long and included a pair of sample points with twenty meters between on the distance 0, 50, 100, 200, 300, 400 and 500 m from the game field. Within each sample point the presence of hardwood trees and shrubs was counted for as well as grazing damage. The study shows that rapeseed is attractive for game species as a food resource. It was a significant difference in biomass between the exclosures and the control plots. The production potential is large, but the rapeseed needs to be fenced during the establishment period. One hectare game field established with rapeseed can produce between 4020 kg and 9950 kg (dry biomass) dependent on the capacity of the game fields. The observation of game species on the game fields in the study shows that roe deer is the most frequent visitor during the observations period. Moose, red deer, fallow deer and wild boars also use the resource, but the observations period is to short too draw any conclusions. The average production on 4020kg (dry biomass) rapeseed per hectare correspond to 335 moose browsing days or 4960 roe deer browsing days. The study shows that the abundance of hard wood trees and shrubs vary with the distance to the game field. It differs between the species in occurrence. In general the occurrence for the broad leaved trees and shrubs is higher in the edge zone and decrease with increased distance to the game field. The browsing pressure is generally high in the edge zone and decrease with increased distance to the game field. However, oak is an exception and which is browsed equally independent of the distance to the game field. High occurrence of desirable hard wood trees and shrubs in the edge zone together with desirable crops on the game fields can attract game species from the surrounding area. The game species can concentrate their food search to the edge zone and the game field. This way it is possible to influence the forage route of game species and thereby also the grazing pressure in the landscape.